2003
DOI: 10.1902/jop.2003.74.12.1771
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic Potential of Fibroblasts from Chronically Inflamed Gingivae Grown in a Hyperglycemic Culture Medium in the Presence or Absence of Insulin and Nicotine

Abstract: Human gingival fibroblasts obtained from chronically inflamed tissue of nondiabetic patients demonstrated that the inhibitory effects of glucose and nicotine on androgen metabolism can be overcome by insulin, in varying degrees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…These results are in accordance with findings in humans that revealed the association between prolonged use of steroids and gingival enlargement 10 . The fact that sub‐ or supraphysiologic levels of testosterone did not influence the gingival area of non‐ligature animals could be at least partially attributed to the inflammation‐induced higher conversion of testosterone to DHT 33,34 . Gingival fibroblasts present androgen receptors (but not estrogen receptors), and DHT upregulates their proliferation 25 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are in accordance with findings in humans that revealed the association between prolonged use of steroids and gingival enlargement 10 . The fact that sub‐ or supraphysiologic levels of testosterone did not influence the gingival area of non‐ligature animals could be at least partially attributed to the inflammation‐induced higher conversion of testosterone to DHT 33,34 . Gingival fibroblasts present androgen receptors (but not estrogen receptors), and DHT upregulates their proliferation 25 .…”
Section: Discussionsupporting
confidence: 89%
“…The effects of testosterone hormone on the periodontium and periodontal cells have been assessed both in humans 8,10 and in vitro, 33,34 but there is insufficient evidence to fully understand the exact effect of testosterone on periodontal tissues and inflammation in general. This issue is important, given the increasing age of most populations and the associated hormonal imbalances 1 .…”
Section: Discussionmentioning
confidence: 99%
“…This case report documents adverse postoperative palatal healing following an SECTG procedure believed to be associated with AAS abuse. While the interactions between AAS and gingival tissues are not well understood, our review of the existing literature 1‐39 supports a physiologic basis for this association. It is our hope that addition of this information to the body of periodontal literature will help make fellow surgeons aware of the widespread recreational abuse of AAS and possible implications that may present in clinical practice.…”
Section: Discussionsupporting
confidence: 54%
“…Modulation of IL‐6 levels has been associated with gingival fibroblast proliferation, especially in the presence of inflammation 34 . Other studies have found that DHT receptor expression is increased in inflamed and hyperplastic gingiva 27‐31 . Studies by Pärssinen et al 35 and Takashiba et al 36 found that exposure to AAS increased Type 1 collagen formation and reduced collagen degradation by fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation